2017
DOI: 10.1016/j.bmcl.2017.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from Sophora tonkinensis and their glucose transporter 4 translocation activities

Abstract: Bioassay-guided phytochemical investigation of the EtOAc fraction (ST-EtOAc) from the roots of Sophora tonkinensis resulted in the isolation of a new compound 6aR,11aR-1-hydroxy-4-isoprenyl-maackiain (1), along with 12 known compounds (2-13). The structure of the new compound was established by 1D and 2D NMR, MS data and circular dichroism analysis. Polyprenylated flavonoids 6-9 and 11-13 increased GLUT-4 translocation by the range of 1.35-2.75 folds. Sophoranone (8) exerted the strongest activity with 2.75 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…Many hypoglycemic agents from natural products have been approved for clinical use in China . Our previous studies have shown that many natural products have the potential to treat DM . Natural products are an important source for possible new drug development for the treatment of DM.…”
Section: Discussionmentioning
confidence: 99%
“…Many hypoglycemic agents from natural products have been approved for clinical use in China . Our previous studies have shown that many natural products have the potential to treat DM . Natural products are an important source for possible new drug development for the treatment of DM.…”
Section: Discussionmentioning
confidence: 99%
“…Then, all insoluble material was discarded and the BCA kit was used to measure the protein concentration. The proteins collected from tissues and cells were subjected to Western blot analysis according to the previously described methods (21).…”
Section: Protein Extracts and Western Blottingmentioning
confidence: 99%
“…It exhibits anti-inflammatory effects by inhibiting nitric oxide production in macrophages [4] and 5-lipoxygenase activity [3]. Several studies have also demonstrated its other biological activities, such as anti-cancer [5], anti-diabetic diabetic [6], and immunomodulatory [7] Figure 1. Chemical structure of (-)-sophoranone (SPN).…”
Section: Introductionmentioning
confidence: 99%